INTERVENSI TEKNIK BIBLIOTERAPI DALAM MENGURANGI PROKRASTINASI AKADEMIK - Athia Tamyizatun Nisa (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
Academic procrastination is related to the tendency to procrastinate and waste time before collection limits associated with school academic activities. Based on the cognitive theory of procrastination behavior caused by cognitive distortions, it is necessary to make efforts to reconstruct the procrastinator's cognitive behavior. It is believed that a behavioral cognitive approach can be applied to manage procrastination and produce substantial improvements. In particular, the technique used is bibliotherapy. The aim of the study was to examine the effectiveness of bibliotherapy techniques in reducing academic procrastination. Implementation of the intervention using the group counseling setting. This study used a pretest-posttest randomized experimental design. Involving the subject as many as 7 class VIII students who were selected purposively. The main instrument used is the Academic Procrastination Scale (APS). Data were analyzed using the Wilcoxon signed rank test statistical test. The results showed that bibliotherapy techniques were effective in reducing academic procrastination of students at Al Abidin Islamic Junior High School, Surakarta.